Case report: Unusual patient with dermatomyositis associated with SARS-CoV-2 infection - Niedzielska, Joanna; Chaszczewska-Markowska, Monika; Chojdak-Łukasiewicz, Justyna; Berezowski, Jakub; Kalra, Seema; Jazwiec, Przemysław (Frontiers in Neurology, 2023)
The severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) outbreak is a major challenge for clinicians. SARS-CoV-2 infection results in coronavirus disease 2019 (COVID-19) and it is best known for its respiratory symptoms. It can also result in several extrapulmonary manifestations such as neurological complications potentially experienced during the course of COVID-19. The association of dermatomyositis (DM) with COVID-19 pathogenesis has not been well-studied. This study aimed to present a previously healthy 37-year-old man, a soldier by profession, with symptoms of DM on the 4th day from the onset of COVID-19. The patient presented DM symptoms with both skin and muscle manifestations. The patient suffered from a cough, fever, and fatigue to begin with and reverse-transcription polymerase chain reaction (RT-PCR) reported positive for SARS-CoV-2 infection. The laboratory findings showed, intra alia, elevated muscle enzymes CK 8253 U/l (N: <145 U/l), a positive test for myositis-specific autoantibodies (anti-Mi-2), electrodiagnostic tests exhibited features of myopathy, with the presence of muscle and skin symptoms. The patient improved with corticosteroids and immunosuppressive agent therapy. In summary, the association between COVID-19 and the development of multi-system autoimmune disorders such as DM remains unclear. Nevertheless, viral infections such as SARS-CoV-2 may likely serve as a trigger.